2013
DOI: 10.1002/jmr.2331
|View full text |Cite
|
Sign up to set email alerts
|

A selective molecularly imprinted polymer-carbon nanotube sensor for cotinine sensing

Abstract: Conductive composite films comprised of single-walled carbon nanotubes coated with molecularly imprinted poly-4-vinylphenol are produced and characterized using ultraviolet and infrared spectroscopies, confirming the successful molecular imprinting of the film with cotinine. The electrical resistance of the imprinted film changes significantly upon binding cotinine, by more than 30 kΩ, while the unimprinted film in comparison elicits little response. Additionally, once the cotinine template desorbs from the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Recent research has indicated that cotinine is a reliable indicator of smoke exposure [10][11][12][13][14] and that median concentrations of cotinine in human saliva are approximately 13.6 nM in non-smokers, 20.4 nM in those affected by secondhand smoke, and 40-74 nM in smokers depending upon various factors such as gender, age, and smoke exposure duration/intensity (e.g., number of cigarettes smoked) [15]. Such cotinine concentration measurements are typically obtained from laboratory techniques such as liquid/gas chromatography, piezoelectric microgravimetry, surface plasmon resonance (SPR), or chemiluminescence immunoassays [16][17][18][19][20][21][22]. These laboratory techniques are generally time consuming and expensive as they require extensive sample preparation and cleanup as well as specialized personnel and instrumentation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has indicated that cotinine is a reliable indicator of smoke exposure [10][11][12][13][14] and that median concentrations of cotinine in human saliva are approximately 13.6 nM in non-smokers, 20.4 nM in those affected by secondhand smoke, and 40-74 nM in smokers depending upon various factors such as gender, age, and smoke exposure duration/intensity (e.g., number of cigarettes smoked) [15]. Such cotinine concentration measurements are typically obtained from laboratory techniques such as liquid/gas chromatography, piezoelectric microgravimetry, surface plasmon resonance (SPR), or chemiluminescence immunoassays [16][17][18][19][20][21][22]. These laboratory techniques are generally time consuming and expensive as they require extensive sample preparation and cleanup as well as specialized personnel and instrumentation.…”
Section: Introductionmentioning
confidence: 99%
“…Molecularly imprinted polymers (MIPs) are easily prepared, stable, and cheap, and these materials are produced in large quantities with good reusability; they have been used in many different areas such as biological molecules and analytical applications . Studies in recent years have shown that MIPs have received considerable scientific attention in the field of sensors . In addition, MIPs and their combination with piezoelectric sensors such as quartz crystal microbalance (QCM) sensors have been popular for the selective detection of pesticides …”
Section: Introductionmentioning
confidence: 99%
“…The removal of the template molecule from the obtained polymer by simple solvent extraction reveals the complementary binding sites that recognize the template molecule from its structurally similar compounds [ 1 ]. Due to their high mechanical and chemical stabilities, ease of preparation, and suitability for a wide range of operating conditions, molecularly imprinted polymers (MIPs) have been developed in various fields, such as solid phase extraction [ 2 ], chromatographic separation [ 3 ], catalysis [ 4 ], membranes [ 5 ], and sensors [ 6 ].…”
Section: Introductionmentioning
confidence: 99%